2004
DOI: 10.1111/j.1467-9841.2004.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

The learning of spoken French variation by immersion students from Toronto, Canada

Abstract: This study on the learning of sociolinguistic variants by 41 adolescents from a French immersion program in Toronto, Canada, synthesizes the ¢ndings of our research on this topic. This article provides answers to the following questions. First, do the immersion students use the same range of sociolinguistic variants as do speakers of Quebec French, who are used in our research as a ¢rst language (L1) benchmark? Second, do they use variants with the same discursive frequency as do L1 speakers? Third, is their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 26 publications
(15 reference statements)
7
79
0
2
Order By: Relevance
“…Clearly, evidence from L2 learners indicates that variation is an extraordinarily complex and challenging thing to acquire and that a range of outcomes are possible. Mougeon et al (2004) caution against the possibility of predicting outcomes when the input is variable, and our own work in London and Edinburgh seems to confirm this. However, there are several cases in our results that do not seem to be the result of re-ordering or non-replication of variable constraints; instead supralocal constraints seem to have been acquired.…”
Section: Supra-local Constraints?mentioning
confidence: 66%
See 2 more Smart Citations
“…Clearly, evidence from L2 learners indicates that variation is an extraordinarily complex and challenging thing to acquire and that a range of outcomes are possible. Mougeon et al (2004) caution against the possibility of predicting outcomes when the input is variable, and our own work in London and Edinburgh seems to confirm this. However, there are several cases in our results that do not seem to be the result of re-ordering or non-replication of variable constraints; instead supralocal constraints seem to have been acquired.…”
Section: Supra-local Constraints?mentioning
confidence: 66%
“…Mougeon et al (2004) synthesises the results of a large-scale project on the acquisition of 13 sociolinguistic variables among French immersion students. Results from these studies seem to point to the general, but rather weak, conclusion that L2 speakers often display partial mastery of the native-speaker norms of variation, but this generalisation in itself is highly variable.…”
Section: Variation In Learners' Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…While this line of inquiry is not new (e.g. Adamson & Regan 1991, Bayley & Preston 1996, Mougeon & Dewaele 2004, Mougeon, Rehner & Nadasdi 2004, Preston 2000, Tarone 1988, Young 1991, studies on L2 English and French have preceded much of the research on L2 Spanish. Recent work on L2 Spanish has examined variation in copula contrast, mood distinction and subject expression across tasks (Geeslin 2003, Geeslin & Guijarro-Fuentes 2006, Gudmestad 2006, 2008, Geeslin & Gudmestad 2008a, 2008b), yet other structures remain to be investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Such studies tend to focus on Type 2 variation, which Mougeon, Rehner & Nadasdi (2004, p. 409) define as "aspects of the target language where native speakers display sociolinguistic variation, that is they alternate between variants". Mougeon et al (2004) investigated a range of variables in the speech of adolescent school students in French immersion education in Canada, where over 50% of the teaching is delivered in French, and found that variation patterned differently in their speech when compared to corpora of native speakers.…”
Section: The Role Of the Peer Groupmentioning
confidence: 99%